2021
DOI: 10.21037/gs-21-380
|View full text |Cite
|
Sign up to set email alerts
|

Management of invasive ductal carcinoma in hypermobile Ehlers-Danlos syndrome: a case report

Abstract: Literature is sparse regarding the management and long-term outcomes of breast cancer in patients with Ehlers-Danlos syndrome (EDS). Of the EDS subtypes, hypermobile Ehlers-Danlos Syndrome (hEDS) is associated with cardiovascular dysautonomia which manifests as spontaneous episodes of tachycardia and hypotension. Given this clinical autonomic system impact, hEDS is known to have significant intraoperative risk and postoperative complications. However, outcomes of hEDS patients have not been specifically studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…An in vitro experiment by Aghajanyan et al found increased radiation-induced chromosomal aberrations in irradiated lymphocytes of children with EDS when compared to that of control subjects, thus raising concerns about increased radiation damage to normal tissues [13]. However, apart from the aforementioned report by Holodny et al, all other case reports did not note any increased radiation toxicity and included radiation to a variety of sites including the axilla, supraclavicular fossa, mediastinum, breast, and brain [4][5][6][7][8][9]. To the best of our knowledge, the current report presents the highest number of case series to date, with the longest duration of follow-up, of women with EDS and breast cancer, treated with adjuvant conventional and hypofractionated radiation therapy to the breast.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An in vitro experiment by Aghajanyan et al found increased radiation-induced chromosomal aberrations in irradiated lymphocytes of children with EDS when compared to that of control subjects, thus raising concerns about increased radiation damage to normal tissues [13]. However, apart from the aforementioned report by Holodny et al, all other case reports did not note any increased radiation toxicity and included radiation to a variety of sites including the axilla, supraclavicular fossa, mediastinum, breast, and brain [4][5][6][7][8][9]. To the best of our knowledge, the current report presents the highest number of case series to date, with the longest duration of follow-up, of women with EDS and breast cancer, treated with adjuvant conventional and hypofractionated radiation therapy to the breast.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen vascular disorders have also been implicated in increased incidence and severity of radiation toxicities [3]. However, there have been few case reports on the safety of radiation therapy with EDS, and most case reports have a very limited duration of follow-up and have used conventional fractionation [4][5][6][7][8][9]. Table 3 compares the current report with available MEDLINE (Medical Literature Analysis and Retrieval System Online)-indexed case reports of patients with EDS who have received radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation